Role of Apparels in Burns due to Domestic Violence – A tool for assessing Degree of Burns - Zulfiqar Ali Buzdar, Mubarak Mehmood Ahmad Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Human life is subject to certain environmental, cultural and ethnic origin factors. Based upon the above facts loose and tight variety of clothing/apparel are commonly used. Fire and flames are an integral part of human life on the other hand and accidents do occur in natural course of history. In such accidents type of apparel one might be wearing play a great role in degree or severity of burns. Association and assessments need to be established in this regard. Methods: The study has been conducted on 250 cases of dry flame burns in AED of Mayo Hospital Lahore/Medicolegal Clinic of King Edward Medical University Lahore for a period of nine months in 2017-18. The population of 250 cases were selected through convenient non-probability purposive sampling technique. The study descriptive cross-sectional study design was applied to the above population selected for the study. Results: Our study revealed1.6% females were involved more than males in the burn incident during the period of study. A wide majority up to 70% used Shalwar and Kameez of loose wearable category as per culture of the country in comparison to the relatively tight clothing of Trousers and Pantaloons variety. A grossly significant role has been established with a p value of 0.024 that loose variety of apparel are responsible for causing greater degree of damage in burns as compared to that of tight variety of apparel worn at the time of incidence. Conclusion: The study concludes that wearing relatively short apparels or of tight i.e. Trousers and Pantaloons variety can be safe, protective and a healthy habit during cooking, working in fire burning vicinity like that of industry, hotels, restaurants and winter outdoor activities. The loose variety hereafter referred as Shalwarand Kameezvariety of cultural apparels can be dangerous and even life threatening when it involves higher percentages of burns. Keywords: Burns, Apparel, Clothing, Degree of Burns